Methodological meta-approach to Design Thinking on a professional master's degree in design: experience report (Revista de Ensino em Artes, Moda e Design, 2025)
The discipline Topics in User-Centered Design, part of the Professional Master's Degree of the Postgraduate Program in Design (PPGD) of the Federal University of Amazonas (UFAM), has as its syllabus the application of innovative methodologies for the creation, concept, development and prototyping of products, considering the needs of users. Among these, this report focuses on the Design Thinking (DT) method, due to its relevance in graduate studies in the field—according to recent Brazilian studies. As an experiment, the course instructor provided instruction on the DT process, as well as the techniques and tools for implementing it, challenging the class to use it to explore a better understanding of their own dissertations, thus establishing a methodological meta-approach to DT. This theoretical-practical research is an exploratory, applied, and qualitative case study, whose objective is to describe the experience of applying DT to facilitate the teaching-learning process and the development of design projects. The example presented is the experience report of a student who applied the focus group technique with her classmates. The results demonstrate that the student transcended her understanding of her project, which allowed her to develop skills required for both research and the job market. Therefore, this article highlights how applying the DT methodology in a classroom practice, through real projects, can be constituted as a concrete pedagogical resource in the teaching-learning process and integrate theory and practice in promoting learning by doing.
Keywords: methodological approach; design; user-centered design; design thinking; professional master's degree